Behavioural Risk Factors of Non-Communicable Diseases among Rural Population in a Selected Area of Dhaka City (Journal of Current and Advance Medical Research, 2022)
Background: Non-communicable diseases (NCDs) is considered as an emerging public health problem recognized as threats.Objective: The purpose of the present study was to determine the behavioural risk factors of non-communicable diseases (NCD) and socio-demographic factors among rural population in Bangladesh.Methodology: This descriptive type of cross sectional study was conducted among 186 participants who were selected purposively in Keranigonj Upazila of Dhaka District and lasted for 15 days from 15th May to 30th May 2019. The data was collected by using a semi structured questionnaire employing purposive technique.Results: A total number of 186 respondent’s were recruited for this study. Regarding physical activity 118(73.75%) of the respondents do physical work 5 to 10 hours per day. Majority of the respondents (48.92%) use table salt whereas 17(9.13%) cases should not. Regarding smoking among male respondents of 41(53.24%) cases were current smokers. Regarding smokeless tobacco 111(59.67%) respondents were current users 64(34.40%) were non-users. Current study showed 14(18.18%) females and 11(10.09%) males were overweight (BMI>25kg/m2). Knowledge regarding risk factors about NCD study showed that knowledge regarding diabetes, cancer and hypertention respondent gave multiple response. Again 76(40.86%) respondents gave the history excess sweet intake and 69(37.09%) respondents for smoking 17(9.13%) had no idea, 77(41.39%) respondents responed hypertention is due to smoking 42(22.58%) respondents had no knowledge about cancer and 71(38.17%) respondents responsed due to intake of unhealthy diet whereas 58(31.18%) they did not about the risk factor of cancer.Conclusion: The increasing burden of noncommunicable diseases (NCDs) in different population groups urges continuous survey to exclude risk factors. In the study area increasing awareness about NCDs through accepted and appropriate strategies need to be implemented.Journal of Current and Advance Medical Research, January 2022;9(1):9-15